Identification and antimicrobial susceptibility testing of Streptococcus agalactiae associated urinary tract infections using VITEK 2 system - Parviz Mohajeri; Hossein Faridafshar; Sara Kooti (Iranian Journal of Microbiology)
Background and Objectives: As a Gram-positive bacterium, Streptococcus agalactiae or Group B Streptococcus (GBS) is normally found as a transient flora of the gastrointestinal and genitourinary tracts of women. The high prevalence of GBS in the urethra warrants investigation of UTIs and antibiotic resistance frequency associated with GBS. Given the paucity of research on antibiotic resistance of GBS in Iran, the present study investigated the UTIs associated with GBS and the antibiotic susceptibility patterns associated with GBS. Materials and Methods: This study included 65 GBS strains collected from urine samples obtained from the Bouali Laboratory Complex, one of the largest laboratories in western Iran. VITEK 2 GP ID cards were used to identify all GBS isolates. VITEK 2 susceptibility testing for Gram-positive bacteria was performed according to the manufacturer's instructions using the AST-ST card. MIC method was performed after the detection of GBS strains. Results: We found that 53 (81.5%) of the GBS isolates showed resistance to tetracycline; 47 (72.3%), 40 (61.5%), and 30 (46.15%) of these had a resistance to erythromycin, clindamycin and ampicillin respectively. Conclusion: In the present study, the VITEK 2 system was validated as a user-friendly system that can serve as a rapid and accurate tool for identification and antimicrobial susceptibility testing of GBS.